Marcadores de recambio óseo en mujeres postmenopáusicas: utilidad clínica - Barberán M., Marcela; Díaz G., Patricia; Liberman G., Claudio; Garrido P., Maritza (Revista Hospital Clínico Universidad de Chile, 2016)
Bone metabolism is a dynamic process, which includes formation and resorption. Osteoblast and osteoclast are responsible of replacing 20% of bone each year. Bone Markers are fragments of bone matrix; these peptides are released in the process of formation and resorption, later accumulated in body compartments (bone and blood) and finally excreted in the urine, reflecting bone dynamic. The international Federation of Osteoporosis and the International Federation of Laboratory and Clinical Chemistry recommend the use of these two markers (one representing bone formation and the other bone resorption) to evaluate bone turnover, especially in high-risk groups such as postmenopausal women. The collagen C-terminal telopeptide or carboxi-terminal collagen crosslinking (CTX) is one of the most used, among different bone markers. This is a blood biomarker that can be measured to assess bone turnover; this marker increases when the bone resorption is accelerated. On the other hand, osteocalcin (a non-collagen protein) is a bone formation marker, which has been widely studied and can be measured in venous blood during bone formation. Both markers are important for monitoring anti-resorptive therapy, and they have been validated to predict fracture risk complementing densitometry in osteoporosis diagnosis. Main disadvantages are variability of the laboratory techniques and lack of information about normal reference values in different populations. Therefore it is necessary to establish normal reference values for each population before its incorporation as a clinical tool.